ANALISIS SENTIMEN PADA TWITTER TENTANG ISU PERILAKU ANTISOSIAL DENGAN ALGORITMA NAÏVE BAYES - Retika Nur Fadila; Andri Triyono; Dhika Malita Puspita (LPPM Universitas An Nuur, 2024)
In 2023, around 78.19% of the 275.77% or 215.63 million Indonesian population will be connected to the internet, with positive impacts such as fast communication, entertainment and new knowledge. The internet makes non-cash transactions easier and has negative impacts such as addiction and antisocial behavior such as indifference to people around you. Teenagers often access social media, especially Twitter, to express opinions and vent both positive and negative. Sentiment analysis is used to determine opinions about antisocial behavior on Twitter by using text mining techniques to analyze teenagers' opinions. Naive Bayes and SVM algorithms are used in sentiment analysis on the Twitter dataset to analyze antisocial behavior. Actions to evaluate the Naive Bayes algorithm in assessing antisocial behavior sentiments had the best accuracy results of 59.71% with k=7 without n-grams. The Naïve Bayes algorithm with k=5 and n-gram n=2 has the best precision of 33.76% and the best recall of 33.45%. Future research can try to use other classification algorithms such as KNN, SVM, etc. To find the best accuracy of the antisocial behavior dataset.